2018
DOI: 10.1186/s12884-018-1876-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of health personnel of maternities in the prevention of mother-to-child transmission of HIV in a sub-Saharan African region with high transmission rate: some solutions proposed

Abstract: BackgroundHigh mother-to-child (MTC) transmission rate of HIV might contribute to the increased pandemic rate. The aim of this study was to identify the knowledge, attitude and practices of health personnel working in maternities in the prevention of MTC transmission of HIV.MethodsThis cross-sectional descriptive study was carried out from 20th February to 30th April, 2017. All health personnel working in the maternity wards were included in this study. The variables recorded included their age, grade, experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
1
18
2
Order By: Relevance
“…These findings was poorer than that reported from recent studies among health workers Nigeria and South Africa [17,29,30]. The results of this study were however similar to other studies which reported an insufficient knowledge among health workers of HIV transmission and strategies for prevention of MTCT [31][32][33][34].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…These findings was poorer than that reported from recent studies among health workers Nigeria and South Africa [17,29,30]. The results of this study were however similar to other studies which reported an insufficient knowledge among health workers of HIV transmission and strategies for prevention of MTCT [31][32][33][34].…”
Section: Discussioncontrasting
confidence: 66%
“…In previous studies, significant associations were described between the level of knowledge of PMTCT and factors such as age, profession, duration of post qualification experience, training, gender, previous training on PMTCT and midwifery qualification [17,29,30,31,36]. Though most of the respondents in our study had received training on PMTCT of HIV and infant feeding counselling for HIV-infected mothers, none of these factors were found to be independently associated with knowledge at both univariate and multivariate regression levels.…”
Section: Discussioncontrasting
confidence: 49%
“…A total of 183 HPs were enrolled in the study, with the median age of 37 years (IQR, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Less than a quarter (19%) were male.…”
Section: Pmtct Knowledge and Practices Of Health Providers Descriptio...mentioning
confidence: 99%
“…High rates of mother-to-child HIV transmission (MTCT) may contribute to an increase in pandemic rates. Research conducted by Nkwabong et al (2018) stated that knowledge is very important in implementing PMTCT program policies by midwives and has a significant influence (AOR= 9.01; 95% CI= 1.82 to 48.60).…”
Section: The Effect Of Midwife Knowledge On the Implementation Of Pmtct Prog Rammentioning
confidence: 99%